Life and absence of rights urban indigenous people: : a case study with the Xavante in Barra do Garças, MT - Dantas , José Elenildo Leite (2024)
The present study aimed to understand the socioeconomic and cultural situation of the Xavante people living in the town of Barra do Garças, MT. In the state of Mato Grosso, the indigenous population, according to IBGE (2022a) is 58,231, and 4,493 of them live in Barra do Garças (IBGE, 2023). It is well-known that indigenous migration to urban areas represents a challenging decision for these peoples, who maintain specific ways of life within their territories. This qualitative research was carried out as a case study and included fieldwork, with interviews and photographic documentation, essential methodological procedures. The study revealed dissatisfaction of the Xavante people with public services provided by municipal, state and federal governments, as well as non-indigenous populations' prejudice against the Xavante, living in precarious housing conditions and experience segregation in public spaces.